1962
DOI: 10.1246/bcsj.35.1276
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of the Formation of Calcium Carbide in a Solid-Solid Reaction

Abstract: The kinetics of the formation of calcium carbide in the solid state reaction of calcium oxide with carbon has been examined by using a thermobalance in the temperature range 1600 to 1800°C and at 50, 100 and 200 mmHg of carbon monoxide. The reaction ratio vs. time curves were parabolic in all experimental runs, and the reaction followed parabolic kinetics: (1−3\sqrt1−x)2=kt. On the other hand, the decomposition of calcium carbide as a successive reaction occurred from the specimen surface and was described as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 1 publication
3
37
1
1
Order By: Relevance
“…Owing to the high purity of the resulting product, the authors suggested that 11 C‐ and 13 C‐enriched alkynes could be prepared by using this method. The solid‐phase synthesis of calcium carbide by the reaction between calcium oxide and carbon was also studied …”
Section: Methods For the Preparation Of Calcium Carbidementioning
confidence: 75%
“…Owing to the high purity of the resulting product, the authors suggested that 11 C‐ and 13 C‐enriched alkynes could be prepared by using this method. The solid‐phase synthesis of calcium carbide by the reaction between calcium oxide and carbon was also studied …”
Section: Methods For the Preparation Of Calcium Carbidementioning
confidence: 75%
“…Electrothermal process is the major technology to synthesize calcium carbide, however, it is a process with high energy consumption and high pollution which depends on its reaction mechanism [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The two reacting solids model has been the typical approach to describe the kinetics of calcium carbide formation. In this model, Tagawa and Sugawara [101] assumed that r k can be expressed as an Arhennius rate expression having the following equation:…”
Section: Cac 2 : Reaction Kinetics and Behaviormentioning
confidence: 99%